Reproductive isolation between two darter species is enhanced and asymmetric in sympatry. Issue 5 (11th April 2014) - Zhou, M.; Fuller, R. C.
<x xml:space="preserve">Abstract</x> Robust reproductive isolation was found between the rainbow darter Etheostoma caeruleum and the orangethroat darter Etheostoma spectabile, as more offspring were produced when conspecific males and females were crossed as compared with heterospecific crosses. Furthermore, fewer eggs resulted from heterospecific crosses involving sympatric E. spectabile females than those using allopatric E. spectabile females, while a similar pattern was not observed in heterospecific crosses using E. caeruleum females. These results suggest that reinforcement, i.e. selection for pre‐zygotic reproductive barriers driven by reduced hybrid fitness, may have contributed to the evolution and maintenance of reproductive barriers between these potentially hybridizing species in sympatry.